Bond strength of HEMA-free and HEMA-containing adhesives under pulpal pressure - Mahdan, Mohd. Haidil Akmal; Masatoshi, Nakajima; Junji, Tagami (2012)

(untitled)
Objectives: To evaluate the effect of simulated pulpal pressure (PP) on initial bond strength of one-stsep self-etch adhesives with different smear layer preparation. Methods: Flat coronal dentin surfaces were obtained from extracted molar teeth .Smear layers were created by grinding with either #180 or #600 grit paper. A HEMA-free one-step self-etch adhesive, Xeno V (XV; Denstply,Germany) and a HEMA-containing adhesive, Tokuyama Bond Force (TBF;Tokuyama Corporation,Japan) were applied to the dentin surfaces according to the manufacturer's instructions under a hydrostatic pressure of 0 or 15 cmH2O. Specimens bonded under 0 cmH20 pressure was served as a control group. After coronal build up with composite resin (CLEARFIL AP-X), the specimens were stored in water at 370C for 24 hour. Bond strength to dentin were determined using microtensile bond (TBS) testing and all data were statistically analyzed using one-way ANOVA (materials and experimental conditions) and additional t-test. Results: The bond strength values (TBS) results table are as follows.